Learning to teach English in the secondary school : a companion to school experience - Davison, Jon, ....-; Dowson, Jane, 1955- (London : Routledge, 2014)
How do you approach teaching English in the contemporary classroom? What is expected of a would-be English teacher? The fourth edition of this best-selling text combines theory and practice to present an indispensable introduction to the opportunities and challenges of teaching English in the secondary classroom. It offers insight into the history, policies and definitions surrounding the subject, together with innovative and practical strategies which can be used for effective teaching and learning. Already a major text for many university teacher education courses, the new edition reflects the extent and impact of current reforms whilst retaining its focus on what is of enduring value for English teaching.? With an emphasis on developing your own values and on stimulating approaches that underpin English teaching, it will help you navigate your way through changing curriculum requirements, assessment practice and the demands of professional development.?? Key topics explored include: Reading, writing and speaking and listening Teaching language and grammar Drama in English teaching Poetry Working with digital technologies Post-16 English language and literature Developing as a critically reflective practitioner. Written particularly with the new and student teacher in mind, Learning to Teach English in the Secondary School aims to equip readers with the tools to make critically informed judgements about how to teach, develop principled practice and most importantly, be mindful of pupils and their experience of English in the secondary classroom.
Keywords: English language -- Study and teaching (Secondary) -- Great Britain; English literature -- Study and teaching (Secondary) -- Great Britain; English teachers -- Training of -- Great Britain; Lerarenopleiding -- (vak)didactiek talen